(untitled) (Journal of Health Sciences, 2021)
The study of anatomy supported with human dissection is foundational to training of health science professionals. For a student, cadaver dissection offers an active learning experience. For the training of physical therapists, we created a manual that efficiently instructs the dissection of the whole body over the course of 30 laboratory periods. In the spirit of academic collegiality, this letter provides health science educators a direct download link (https://hdl.handle.net/11299/218174) to the dissection manual hosted by the University of Minnesota (USA) Digital Conservancy. No registration is required, the download is free, and the PDF file of the dissection manual can be reproduced or adapted for any educational use.